Epicardial left ventricular lead implantation in cardiac resynchronization therapy patients via a video‐assisted thoracoscopic technique: Long‐term outcome. Issue 3 (14th December 2019) - Marini, Massimiliano; Branzoli, Stefano; Moggio, Paolo; Martin, Marta; Belotti, Giuseppina; Molon, Giulio; Guarracini, Fabrizio; Coser, Alessio; Quintarelli, Silvia; Pederzolli, Carlo; Graffigna, Angelo; Penzo, Daniele; et al.
Abstract: Background: Epicardial placement of the left ventricular (LV) lead via a video‐assisted thoracoscopic (VAT) approach is an alternative to the standard transvenous technique. Hypothesis: Long‐term safety and efficacy of VAT and transvenous LV lead implantation are comparable. To test it, we reviewed our experience and we compared the outcomes of patients who underwent implantation with the two techniques. Methods: The VAT procedure is performed under general anesthesia, with oro‐tracheal intubation and right‐sided ventilation, and requires two 5 mm and one 15 mm thoracoscopic ports. After pericardiotomy at the spot of the epicardial target area, pacing measurements are taken and a spiral screw electrode is anchored at the final pacing site. The electrode is then tunneled to the pectoral pocket and connected to the device. Results: 105 patients were referred to our center for epicardial LV lead implantation. After pre‐operative assessment, 5 patients were excluded because of concomitant conditions precluding surgery. The remaining 100 underwent the procedure. LV lead implantation was successful in all patients (median pacing threshold 0.8 ± 0.5 V, no phrenic nerve stimulation) and cardiac resynchronization therapy was established in all but one patient. The median procedure time was 75 min. During a median follow‐up of 24 months, there were no differences in terms of death, cardiovascular hospitalizations or device‐related complications vs the group of 100 patients who had undergone transvenous implantation. Patients of both groups displayed similar improvements in terms of ventricular reverse remodeling and functional status. Conclusions: Our VAT approach proved safe and effective, and is a viable alternative in the case of failed transvenous LV implantation.